POTENSI ANTI-INFLAMASI DAN KADAR FLAVONOID TOTAL EKSTRAK ETIL ASETAT DAUN KOKANG (Lepisanthes amoena) YANG DIEVALUASI DENGAN METODE INHIBISI DENATURASI PROTEIN - Fadlilaturrahmah; Arnida; Amalia Khairunnisa; Normaidah; Mifthah Dwi Arini (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Kokang (Lepisanthes amoena) is an endemic plant from Kalimantan traditionally used by the Dayak Tunjung community for skincare and wound treatment. Empirically, its leaves accelerate healing of skin problems such as acne scars and wounds within approximately two weeks. This research aimed to determine the total flavonoid content and evaluate the anti-inflammatory potential of the ethyl acetate extract of L. amoena leaves using the protein denaturation inhibition assay. The total flavonoid content was quantified spectrophotometrically using the aluminum chloride method, expressed as quercetin equivalents (QE). Anti-inflammatory activity was assessed by measuring the inhibition of protein denaturation, with sodium diclofenac as a positive control, and IC₅₀ values were calculated to compare activity levels. The results showed that the yield of the ethyl acetate extract of L. amoena leaves was 1.77%, with a total flavonoid content of 143.496 mg QE/g extract, and that it exhibited strong anti-inflammatory activity with an IC₅₀ value of 16.759 ppm. These findings scientifically support the traditional use of L. amoena leaves as an anti-inflammatory and wound-healing agent, highlighting their potential development for herbal or cosmeceutical formulations.